2014
DOI: 10.3109/02713683.2014.898311
|View full text |Cite
|
Sign up to set email alerts
|

Interexaminer Reproducibility of Optical Coherence Tomography for Measuring the Tear Film Meniscus

Abstract: We showed a strong statistical agreement for both TMA and TMH measurements. According to our results, we believe that FD-OCT device is dependable in measuring the TMA and TMH values, given that its results are reproducible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 25 publications
1
20
0
2
Order By: Relevance
“…12,30 These results are in agreement with our study. In this study, we also found the TMH measured with the keratograph to be repeatable and reproducible on a similar level to FD-OCT. Good repeatability and reproducibility were demonstrated by a low intraexaminer (6.4% and 6.5%, respectively) and interexaminer CoV% (5.6%) and the high overall ICCs (98.7% and 98.6%, respectively).…”
Section: Discussionsupporting
confidence: 93%
“…12,30 These results are in agreement with our study. In this study, we also found the TMH measured with the keratograph to be repeatable and reproducible on a similar level to FD-OCT. Good repeatability and reproducibility were demonstrated by a low intraexaminer (6.4% and 6.5%, respectively) and interexaminer CoV% (5.6%) and the high overall ICCs (98.7% and 98.6%, respectively).…”
Section: Discussionsupporting
confidence: 93%
“…Points on the grading scale that did not occur in any group are not shown. Palakuru et al 2007Palakuru et al , 2008Ibrahim et al 2010;Koh et al 2010;Chen et al 2011;Park et al 2012;Qiu et al 2012;Altan-Yaycioglu et al 2013;Fukuda et al 2013;Bartuzel et al 2014;Canan et al 2014;Sizmaz et al 2014;Akiyama et al 2015;Tukenmez-Dikmen et al 2015). For measuring precorneal tear film, the resolution of commercially available OCT systems is not sufficient for quantitative measurement.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have shown repeatability and reproducibility in using OCT to measure TMA and TMD. 120,122 They also have been shown to correlate with DED and traditional measurements for DED. 116,119,120 However, TMA and TMD measurements using OCT have not yet been incorporated in any multicenter clinical trial.…”
Section: Point Of Care Biomarkersmentioning
confidence: 93%
“…97,110120 Some studies suggest there is good repeatability and reproducibility of TMH measurements in DED and normals. 101,114,115,118,120122 However, TMH taken with different machines may not be comparable. 111,115,121 …”
Section: Point Of Care Biomarkersmentioning
confidence: 99%